Security system of an electric motorcycle based on Gsm & Zigbee communication - Palchaudhuri, Arkoalo; T Manimegalai, C (International Journal of Engineering and Technology, 2018)
The time has come that people need to think about saving fuel seriously because burning too much of fuel can cause a large number of environmental pollutions. The concept of making the battery operated electric vehicle comes as a rescue. In one hand it helps to save fuels and on the other it helps in lowering the level of air pollution; which helps in improving the health condition of the populace. Even though several automobile manufacturers have introduced Hybrid Vehicles (hybrid vehicles generally utilize a traditional combustion engine and a fuel tank, as well as one or more electric motors and a battery pack).This paper is going to propose an electric motorcycle security system based on ARM microcontroller, 8051 microcontroller, ZigBee and GSM communication which can be utilized both in Hybrid motorcycles and Electric motorcycles. When the proposed security features will be merged with those vehicles it will be an evolutionary concept in the world of next generation two-wheeler industry because besides lowering the level of air pollution and helping in controlling the use of fuel it mainly helps people to drive motorcycles safely.